2003
DOI: 10.1021/es026151e
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Sorption Domains in Soil Organic Matter Using Structurally Modified Humic Acids

Abstract: The sorption of phenanthrene was examined in humic acids (HAs) from different sources: a compost, a peat soil, and a mineral soil. Sub-samples of each HA were subjected to bleaching or hydrolysis to remove predetermined chemical groups from their structures. Bleaching successfully removed a large percentage of rigid, aromatic moieties, whereas hydrolysis removed the mobile, carbohydrate components. Phenanthrene sorption by all HAs was nonlinear (N < 1). However, the phenanthrene isotherms of the bleached HAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
85
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 36 publications
(53 reference statements)
10
85
0
1
Order By: Relevance
“…The rigidity of a macromolecular structure was reflected by the glass transition temperature T g , which has been discovered for humic acids with differential scanning calorimetry analysis and ranged between 43 and 72°C (Schaumann and Antelmann, 2000;Katherine et al, 2000;LeBoef and Weber, 2000;Young and LeBoeuf, 2000). According to the temperature isotherms below the T g of humic acid in this study, the structure and properties of the humic acid should be unchanged (Gunasekara, 2003). It may be the reason for the similarity of TII values observed at 5, 25, and 35°C.…”
Section: Sorption and Desorption Of Pfos To Humic Acid At Different Tmentioning
confidence: 61%
“…The rigidity of a macromolecular structure was reflected by the glass transition temperature T g , which has been discovered for humic acids with differential scanning calorimetry analysis and ranged between 43 and 72°C (Schaumann and Antelmann, 2000;Katherine et al, 2000;LeBoef and Weber, 2000;Young and LeBoeuf, 2000). According to the temperature isotherms below the T g of humic acid in this study, the structure and properties of the humic acid should be unchanged (Gunasekara, 2003). It may be the reason for the similarity of TII values observed at 5, 25, and 35°C.…”
Section: Sorption and Desorption Of Pfos To Humic Acid At Different Tmentioning
confidence: 61%
“…In contrast, pyrene displayed a strong nonlinear sorption isotherm on a degraded lignin (Chefetz et al, 2000). Gunasekara et al (2003) observed that Phen sorption isotherms were more linear on bleached humic acids that had lignin removed structurally than on the corresponding untreated humic acids. Hence the sorption mechanism of HOCs on lignin is still under discussion.…”
Section: Introductionmentioning
confidence: 92%
“…3.1). Numerous studies have provided evidence for proportional relationships between the amount of contaminant sorption and OM aromaticity (Xing 2001;Gauthier et al 1987;Perminova et al 1999;Chefetz et al 2000;Chin et al 1997), specific OM domains (Salloum et al 2000;Gunasekara et al 2003;Simpson et al 2003;Mao et al 2002), and/or OM polarity (Xing et al 1994b;Gauthier et al 1987;Grathwohl 1990;Kopinke et al 2001). In addition to this, several reports suggest that the physical conformation (as illustrated in Fig.…”
Section: The Role Of Organic Matter-mineral Interactions In Organic Cmentioning
confidence: 99%
“…Simpson et al (2003) also reported an increase in phenanthrene sorption to HA after the selective removal of carbohydrates and aromatic components. Gunasekara et al (2003) found that these chemical extractions resulted in a more A decrease in isotherm nonlinearity was also observed, suggesting that the removal of aromatic structures "opened up" mobile, liquid-like regions and rendered these domains more accessible to contaminants (Gunasekara et al 2003). A mass balance approach has also been used to test the role of OM conformation in contaminant sorption processes (Salloum et al 2001;Bonin and Simpson 2007a).…”
Section: The Role Of Organic Matter-mineral Interactions In Organic Cmentioning
confidence: 99%